Planificación para la conservación de sitios en el campus Salache. - Auquilla Ordoñez, Karen Andrea (2022)
The Salache campus of the Technical University of Cotopaxi has several anthropogenic activities that have influenced the lack of conservation in the natural areas of this campus, for this reason, in this study, a planning proposal for the conservation of the campus was developed through appropriate strategies. This was done through the application of the methodology described in the Conservation Area Planning Manual presented by ‘The Nature Conservancy’. The first step was to carry out a diagnostic study to determine the existence of several areas, selecting the “Casa Hacienda” as the study area to be prioritized. Determining the viability of conservation, identifying 2 conservation targets as support services to the habitat of species and as cultural services to recreation, mental and physical health activities. For this purpose, key ecological attributes and indicators were identified and it was necessary to apply the Margalef Index, which showed that there are currently 3 individuals per bird species, 15% of bare soil and 30% of covered soil, and the effective load capacity shows 5,508.27 visits within the recreation areas. In the same way, pressures such as habitat fragmentation, loss of bird species, and the presence of solid waste which are affecting objects according to their severity and scope were analyzed and determined as well as the sources of pressure that were rated based on their contribution and irreversibility resulting in the direct threats to the objects are hiking, the introduction of exotic species and overload of beneficiaries which have taken the value identified as ‘HIGH’; the campus has conservation elements that can improve its current state of conservation, this would be reflected if the strategies were implemented, so it is recommended that they be selected and implemented.